Hubungan jenis packed red cell (PRC) yang ditransfusikan dengan reaksi transfusi febrile non haemolytic transfusion reaction (FNHTR) - Dinda Kamilah; Dian Widyaningrum (Intisari Sains Medis, 2019)
Background: One of the components of blood cells are often used for transfusions is Packed Red Cell (PRC). Blood components transfusion may continues with rapid or delayed transfusion ractions. The most transfusion reactions was fever (55%) or febrile non haemolytic transfusion reaction (FNHTRs). The cause of these events is associated with allogenic leucocytes (the ability to differentiate self cells and non-self cells based on the human leukocyte antigen (HLA) on the cell surface) and release of proinflammatory cytokines such as IL-1, IL-6, IL-8, TNFα, Cell-free DNA (cfDNA), histone and the duration of blood storage. Methods: Cross-sectional study on 41.177 patients who received a PRC transfusion with the FNHTR transfusion reaction in Hospital Blood Bank Dr. Kariadi Semarang, during January 2017 to July 2018. Pearson Chi Square test for expected frequency more than 5. The Kolmogorov smirnov and Shapiro-wilk test were used to evaluate normality of the data. Mann-Whitney test to analyze the difference, p < 0,05 was considered as significant.Results: The incidence of FNHTR was lower in patients who received leukodepleted PRC (11 patients) than non leukodepleted PRC (124 patients). There were differences in body temperature in the incidence of FNHTR between the two groups 38.10 C (38-39) VS 38.40 C (38 – 39.2) with p = 0,046.Conclusions:There were relationship between the incidence of FNHTR with the transfusion with leukodepleted PRC and non leukodepleted PRC.